2020
DOI: 10.3390/brainsci10030178
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia Might Influence the Thickness of Choroid, Retinal Nerve Fiber and Inner Plexiform Layer

Abstract: Sleep may play a fundamental role in retinal regulation and the degree of retinal variables. However, no clinical study has investigated optical coherence tomography (OCT) parameters in patients with primary insomnia. All participants were evaluated with the insomnia severity index (ISI) and the Pittsburgh sleep quality index (PSQI). The retinal nerve fiber layer (RNFL), ganglion cell layer (GC), inner plexiform layer (IPL), macula and choroidal (CH) thickness were compared between 52 drug-naïve patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…Our average choroidal thickness measures are consistent with previous studies measuring the choroidal thickness in healthy human eyes (20)(21)(22)(23). Shahbaz et al studied the choroidal thickness changes in patients with primary insomnia (24). They reported significant thickening in the choroidal layer in these patients comparing to healthy controls.…”
Section: Discussionsupporting
confidence: 90%
“…Our average choroidal thickness measures are consistent with previous studies measuring the choroidal thickness in healthy human eyes (20)(21)(22)(23). Shahbaz et al studied the choroidal thickness changes in patients with primary insomnia (24). They reported significant thickening in the choroidal layer in these patients comparing to healthy controls.…”
Section: Discussionsupporting
confidence: 90%
“…There are limited data on the effect of different immunomodulatory treatments on retinal integrity, and this could potentially skew our results, as we cannot eliminate the possibility of treatment heterogeneity with different impact on retinal injury [ 33 ]. Furthermore, we did not take into consideration various lifestyle factors, such as race, obesity, sleep duration and quality, and smoking that might interfere with the interpretation of our findings, as they can potentially affect the retinal structure and contribute to RNFL thinning [ 10 , 11 , 12 ]. Moreover, we have not studied any correlations with visual outcomes or serum neurofilament light chain levels that previous reports showed positive correlation with accelerated rates of neuro-axonal loss association in RRMS±ON [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…RNFL is the innermost layer of the retina, consisting of unmyelinated axons originating from the ganglion cell neurons, which enters the neural retinal rim of the optic disc and, subsequently, coalesces as the optic nerve [ 8 ]. Retinal-layer thickness is used to monitor the progression of MS and the effect of modifiable risk factors for MS on retinal health and to mirror cortical atrophy in the MS population [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. More recently, OCT outcomes have been used in clinical trials [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence supports a link between psychiatric disorders and choroidal thickness, regardless of the presence of CSC or another ophthalmological diagnosis: Ayyildiz D and Ayyildiz T (2020) [36] reported a significant thickening of the central choroid in 41 children and adolescents with anxiety disorders compared with HC. Likewise, further evidence indicated that choroidal thickness is significantly increased in adult patients with primary insomnia [37], bruxism [38] and obsessive-compulsive disorder [39]. Regarding insomnia, previous authors suggested that excessive exposure to light, through the increase in retinal dopamine and the subsequent nitric oxide release, may lead to an upper blood flow in the choroid and, ultimately, to its thickening [40].…”
Section: Discussionmentioning
confidence: 99%